2003
DOI: 10.1016/s0020-7292(03)00042-0
|View full text |Cite
|
Sign up to set email alerts
|

Labor induction post-term with 25 micrograms vs. 50 micrograms of intravaginal misoprostol

Abstract: Intravaginal administration of 25 microg of misoprostol appears to be as effective as 50 microg for cervical ripening and labor induction beyond 41 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
26
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 10 publications
8
26
6
Order By: Relevance
“…This is contrast to the finding of Meydanli et al [19] and Elhassan et al [17] Meydanli reported that more women delivered between 12-24 hours in the 25 µg group while El-hassan reported that fewer delivered vaginally in the 25 µg group. The explanation for the differences may be in the methodology.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This is contrast to the finding of Meydanli et al [19] and Elhassan et al [17] Meydanli reported that more women delivered between 12-24 hours in the 25 µg group while El-hassan reported that fewer delivered vaginally in the 25 µg group. The explanation for the differences may be in the methodology.…”
Section: Discussioncontrasting
confidence: 86%
“…Although the study found that induction delivery interval was similar among the two groups, other investigators [13][14][15][16][17][18] had demonstrated that it was shorter in the 50 µg group. In a meta-analysis comparing 25 µg with 50 µg misoprostol, the induction vaginal delivery interval was nearly five hours shorter in the 50 µg group [19]. This difference as against meta-analysis may be due to small sample size and non-blinding of the study.…”
Section: Discussionmentioning
confidence: 94%
“…3 However, the cases with failed induction were more common in low dose misoprostol, these finding was consistent with one of the study of meydanliet et al 4 Their study also reported that the proportion of women delivering vaginally with one dose of vaginal misoprostol was significantly greater in 50 g group (0/49 vs. 41/47;p>0.001) which was not studied in our cases. In a comparative study reported by Has et al showed the rate of Cesarian Section due to fetal distress was higher with higher dose (28.6 vs. 10.3% p>0.05).…”
Section: Resultssupporting
confidence: 91%
“…Neonatal outcome were comparable. Similar to this study neonatal outcome (APGAR and NICU admission) was comparable in lower and higher dose vaginal misoprostol groups in the study by Makbib Diro et al, Ozsoy M, Meydanli MM et al and Kreft M. 10,11,14,15 …”
supporting
confidence: 89%
“…8 Has R et al and Myedanli MM reported similar results that the rate of uterine tachysystole and hyper stimulation syndrome was comparable in both groups. 10,13 In group A (25 mcg misoprostol), 1 minute APGAR <7 was seen in 3 (5.45%) neonates and in group B (50mcg misoprostol), 1 minute APGAR <7 was seen in 8 (14.55%). The difference in APGAR is not statistically significant, P value = 0.2036.…”
mentioning
confidence: 98%